STEM-Based Instrument Integration: Enhancing Systems and Science Skills in Teaching - Likita, Egy Razka; Abdurrahman, Abdurrahman; Hasnunidah, Neni; Jalmo, Tri (Darul Yasin Al Sys, 2024)
This research aims to describe STEM-based practicum instrument componentinstrument to stimulate students' system thinking skills based on the views of teachers and students. This research involved 50 middle school science teachers in Lampung Province. The method used in this research is a mixed method with explanatory sequential design to obtain quantitative and qualitative data through questionnaires and interviews. The results of the research show that teachers and students have a positive perception towards the development of STEM-based practicum instrument component. This research found the fact that there are some difficulties experienced by teachers in the use of STEM-based practicum instrument component. Teachers believe that the use of STEM-based practicum instrument component can stimulate the system thinking ability and have an impact on the improvement of students science process skills.